How natural flood management helps downstream urban drainage in various storm directions. Issue 3 (27th June 2021) - Ferguson, Charlie; Fenner, Richard
Abstract : The wider benefits of natural flood management are increasingly used to engage local stakeholders and justify physical implementation. Previous studies have highlighted the potential for upstream natural flood management interventions to contribute to water level management strategies by mitigating downstream water levels and promoting free discharge at surface drainage outfalls from urban areas. The study reported in this paper extended the scope of this possible benefit by examining the potential for upstream interventions to de-synchronise rural and urban responses under various storm tracks, thereby improving the performance of downstream surface drainage networks. The methodology used a coupled modelling approach. Five design events, each applied with eight different storm tracks, were used to evaluate how catchment-scale natural flood management in the upper Calder River, UK, might influence performance of surface drainage in the downstream town of Todmorden. The results suggested that all the storm tracks considered had substantial influence on whether urban rainfall occurs during the period when outfalls are inundated. While upstream natural flood management interventions create modest flow attenuation, a slight delay in rural response can significantly improve drainage performance and reduce instances of nuisance flooding.